PERAN WALISONGO DALAM PERADABAN ISLAM INDONESIA - Sirojul Fuadi; Ayu ramadani safitri; Amalia Audia; Rini Dalimunthe; Nurmala Siska Dewi; Aditya Ramadhan; Faqih Hidayah Tullah; Ade Syahputra; Abibah Hanum (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to describe clearly and comprehensively the significant role of Walisongo in the Islamisation process in Java, particularly through peaceful methods of proselytising that were well received by the community. This study uses a literature review method, collecting data from various sources, such as history books, scientific journals and writings by historians on the proselytising of Walisongo. The results of the study indicate that the Walisongo successfully spread Islam through cultural, educational, and political approaches without violence. They utilised various media such as mosques, Islamic boarding schools, wayang (shadow puppet theatre), tembang (traditional songs), and gamelan (traditional music) to convey Islamic teachings, and applied gentle da'wah methods such as hikmah (wisdom), mauidzah hasanah (good advice), and al-jidal ahsan (the best form of debate). The saints, such as Sunan Gresik, Sunan Ampel, Sunan Kalijaga, and Sunan Gunung Jati, had different yet complementary missionary strategies, whether through formal education in Islamic boarding schools, social outreach, or spiritual and local cultural approaches. Their success was also supported by their proximity to political power, such as the Majapahit Kingdom and the Demak Sultanate. The cultivation of strong faith, the peaceful establishment of Islamic law, and the development of societal ethics formed the foundation of the Walisongo's missionary success. This success established the Walisongo as central figures in building a peaceful Islamic civilisation in the archipelago, deeply rooted in local cultural traditions.